A hybrid method for inverse scattering for sound-soft obstacles in R3 - Serranho, Pedro (2011)
We present a hybrid method to numerically solve the inverse acoustic soundsoft obstacle scattering problem in R3, given the far-field pattern for one incident direction. This method combines ideas of both iterative and decomposition methods, inheriting advantages of each of them, such as getting good reconstructions and not needing a forward solver at each step. A related Newton method is presented to show convergence of the method and numerical results show its feasibility.